2014
DOI: 10.1021/bi500373k
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Alzheimer’s β-Amyloid Peptides with Cholesterol: Mechanistic Insights into Amyloid Pore Formation

Abstract: Brain cholesterol plays a critical role in Alzheimer's disease and other neurodegenerative diseases. The molecular mechanisms linking cholesterol to neurotoxicity have remained elusive for a long time, but recent data have allowed the identification of functional cholesterol-binding domains in several amyloidogenic proteins involved in neurodegenerative diseases, including Alzheimer's disease. In this review, we analyze the cholesterol binding properties of β-amyloid (Aβ) peptides and the impact of these inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
193
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(203 citation statements)
references
References 156 publications
(321 reference statements)
10
193
0
Order By: Relevance
“…The hypotheses associated with the possible role of cholesterol in the pathogenesis of AD suggest that cholesterol may trigger the synthesis of AB peptide from amyloid precursor protein or increase amyloid plaque formation by lowering the aggregation threshold of AB peptide [44][45][46][47][48][49][50]. Based on our data it may be also suggested that cholesterol could play a key role in AB toxicity as a precursor molecule of steroid hormones.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The hypotheses associated with the possible role of cholesterol in the pathogenesis of AD suggest that cholesterol may trigger the synthesis of AB peptide from amyloid precursor protein or increase amyloid plaque formation by lowering the aggregation threshold of AB peptide [44][45][46][47][48][49][50]. Based on our data it may be also suggested that cholesterol could play a key role in AB toxicity as a precursor molecule of steroid hormones.…”
Section: Discussionsupporting
confidence: 55%
“…Studies in recent years have addressed cholesterol, AB peptides and mitochondria as a dangerous trio for AD [39,45,47,75]. The hypotheses associated with the possible role of cholesterol in the pathogenesis of AD suggest that cholesterol may trigger the synthesis of AB peptide from amyloid precursor protein or increase amyloid plaque formation by lowering the aggregation threshold of AB peptide [44][45][46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico models of oligomeric Aβ(1-40) and Aβ(1-42) have suggested the formation of an acidic central pore involving Glu3, Asp7 and Glu11 (Diaz et al 2006 ). A tetrameric channel was proposed as a model for oligomeric Aβ(1-42) bound to cholesterol in the membrane (Di Scala et al 2014a ).…”
Section: Aβ Toxicity and Perturbation Of Cell Membranesmentioning
confidence: 99%
“…This 418 might be related to the processive cleavage by the γ-secretase, as flexi-419 bility allows the helix to adopt to the sluice-like active site of the prote-420 ase[146][147][148][149]. Importantly, the proteolytic efficiency is enhanced 2-4 421 fold in the presence of cholesterol[150].422In recent studies a cholesterol-binding site and a homodimerization 423 interface at C99 were defined[146,[151][152][153]. Homodimerization and 424 cholesterol binding were found to compete, as both involve the glycine 425 zipper motif G 700 xxxG 704 xxxG 708 G 709[151] (Fig.…”
mentioning
confidence: 99%